Implementation of Saudi Vision 2030 Towards Saudi Arabia’s Internationally Open Tourism Industry - Amelia Pratiwi; Siti Muslikhati (Jurnal Indonesia Sosial Sains, 2024)
The existence of globalization encourages access to worldwide economic development that does not solely rely on one sector, especially in the tourism sector. Saudi Vision 2030, in foreign policy theory, is perceived as Saudi Arabia’s strategy to diversify the country’s economy. The decline in global oil prices has resulted in the swelling of the state deficit. Under the leadership of Prince Muhammad bin Salman, the Saudi Arabian Government undertook efforts to diversify the revenue sector, aiming to reduce the country’s economic dependence on crude oil exports. Through Vision 2030, tourism is prioritized as a significant contributor to state revenue. The development of tourism components and the opening of new tourist destinations are forms of implementation initiated by the government based on the Saudi Vision. This research combines the theory of foreign policy and tourism concepts employed by the government of Saudi Arabia. The qualitative research method uses secondary data from literature studies, including journals, books, official websites, and articles. The results indicate that the realization of Saudi Vision 2030 in the tourism industry is through the development of tourism components in hotels, transportation, and restaurants and the opening of new tourist destinations, specifically in culture and adventure tourism